Interleukin-19 Aggravates Pulmonary Fibrosis via Activating Fibroblast through TGF-β/Smad Pathway - Wang, Yu; Sun, Sibo; Wang, Kai; Zhang, Mingjiong; Li, Min; Zan, Yumin; Huang, Qiqing; Wu, Shuangshuang; Zhao, Weihong; Xu, Wei; Wu, Jianqing (Mediators of Inflammation, 2022)
Background. Idiopathic pulmonary fibrosis (IPF) is a progressive and fatal interstitial pneumonia disease with no cure. Communication between injured cells is triggered and maintained by a complicated network of cytokines and their receptors. IL-19 is supported by increasing evidences for a deleterious role in respiratory diseases. However, its potential role in lung fibrosis has never been explored. Methods. Bioinformatic, immunohistochemistry and western blot analysis were used to assess the expression of IL-19 in human and mouse fibrosis lung tissues. CCK-8, transwell and flow cytometry assay were utilized to analyze the effect of IL-19 on biological behaviors of lung fibroblasts. Histopathology was used to elucidate profibrotic effect of IL-19 in vivo. Results. IL-19 was upregulated in fibrosis lung tissues. IL-19 promoted lung fibroblasts proliferation and invasion, inhibited cell apoptosis, and induced differentiation of fibroblasts to the myofibroblast phenotype, which could be revised by LY2109761, a TGF-β/Smad signaling pathway inhibitor. Furthermore, we found that IL-19 aggravated lung fibrosis in murine bleomycin-induced lung fibrosis. Conclusions. Our results imply the profibrotic role for IL-19 through direct effects on lung fibroblasts and the potential of targeting IL-19 for therapeutic intervention in pulmonary fibrosis.